Peranan Dinasti Idrissiyah dalam Penyebaran Agama Islam di Maroko - Ilma Yuliyana; Dian Falahdita; Haidar Syadad (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
The Idrisid dynasty played a crucial role in the spread of Islam in Morocco during the late 8th century CE. Founded by Idris I, the dynasty successfully unified various Berber tribes under Islamic rule. Through political consolidation, social integration, and cultural development, the Idrisids strengthened the foundations of Islam in the region. They established key urban centers such as Fez, which became a major hub for Islamic scholarship and missionary activities. Their support for education, the construction of mosques, and the promotion of the Zaidi Shia school of thought significantly accelerated the Islamization process among the local population. This article examines the process of Islamic dissemination in Morocco by the Idrisid dynasty, the factors contributing to its success, and the religious and cultural legacy it left behind. Using a historical-analytical approach, the study highlights how the Idrisids not only facilitated the Islamization of Morocco but also laid the groundwork for the broader development of Islamic civilization in the Maghreb region.